Biliary Microbiota, Gallstone Disease and Infection with Opisthorchis felineus - Saltykova, Irina V.; Petrov, Vjacheslav A.; Logacheva, Maria D.; Ivanova, Polina G.; Merzlikin, Nikolay V.; Sazonov, Alexey E.; Ogorodova, Ludmila M.; Brindley, Paul J. (PLOS Neglected Tropical Diseases, 2016)
Background There is increasing interest in the microbiome of the hepatobiliary system. This study investigated the influence of infection with the fish-borne liver fluke, Opisthorchis felineus on the biliary microbiome of residents of the Tomsk region of western Siberia. Methodology/Principal Findings Samples of bile were provided by 56 study participants, half of who were infected with O. felineus, and all of who were diagnosed with gallstone disease. The microbiota of the bile was investigated using high throughput, Illumina-based sequencing targeting the prokaryotic 16S rRNA gene. About 2,797, discrete phylotypes of prokaryotes were detected. At the level of phylum, bile from participants with opisthorchiasis showed greater numbers of Synergistetes, Spirochaetes, Planctomycetes, TM7 and Verrucomicrobia. Numbers of > 20 phylotypes differed in bile of the O. felineus-infected compared to non-infected participants, including presence of species of the genera Mycoplana, Cellulosimicrobium, Microlunatus and Phycicoccus, and the Archaeans genus, Halogeometricum, and increased numbers of Selenomonas, Bacteroides, Rothia, Leptotrichia, Lactobacillus, Treponema and Klebsiella. Conclusions/Significance Overall, infection with the liver fluke O. felineus modified the biliary microbiome, increasing abundance of bacterial and archaeal phylotypes.